2018
DOI: 10.1038/s41598-018-26577-0
|View full text |Cite|
|
Sign up to set email alerts
|

Salvianolic acids from antithrombotic Traditional Chinese Medicine Danshen are antagonists of human P2Y1 and P2Y12 receptors

Abstract: Many hemorheologic Traditional Chinese Medicines (TCMs) that are widely-used clinically lack molecular mechanisms of action. We hypothesized that some of the active components of hemorheologic TCMs may function through targeting prothrombotic P2Y1 and/or P2Y12 receptors. The interactions between 253 antithrombotic compounds from TCM and these two G protein-coupled P2Y receptors were evaluated using virtual screening. Eleven highly ranked hits were further tested in radioligand binding and functional assays. Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 58 publications
2
18
0
Order By: Relevance
“…The reversible and very potent antagonist ACT‐246475 (Caroff et al, 2015) is being tested in clinical trials for use in the prevention or treatment of cardiovascular events (Baldoni et al, 2014). In addition, a variety of moderately potent P2Y 12 receptor antagonists have been described, among them 4‐benzhydrylmorpholines (Ahn et al, 2016), flavonolignans (Bijak, Szelenberger, Dziedzic, & Saluk‐Bijak, 2018), and salvianolic acids (Liu et al, 2018). [ 3 H]PSB‐0413 is an antagonist radioligand, the tritiated form of AR‐C67085 ( 28 ), which binds to P2Y 12 receptors with a K D value of 4.6 nM (Ohlmann et al, 2013).…”
Section: Selective Ligand Tools To Study P2y Receptorsmentioning
confidence: 99%
“…The reversible and very potent antagonist ACT‐246475 (Caroff et al, 2015) is being tested in clinical trials for use in the prevention or treatment of cardiovascular events (Baldoni et al, 2014). In addition, a variety of moderately potent P2Y 12 receptor antagonists have been described, among them 4‐benzhydrylmorpholines (Ahn et al, 2016), flavonolignans (Bijak, Szelenberger, Dziedzic, & Saluk‐Bijak, 2018), and salvianolic acids (Liu et al, 2018). [ 3 H]PSB‐0413 is an antagonist radioligand, the tritiated form of AR‐C67085 ( 28 ), which binds to P2Y 12 receptors with a K D value of 4.6 nM (Ohlmann et al, 2013).…”
Section: Selective Ligand Tools To Study P2y Receptorsmentioning
confidence: 99%
“…Recent researches on the action mechanisms of SAA have found that SAA can antagonize the activity of both [27]. Moreover, pretreatment with SAA on platelets caused an increase in the cAMP level in platelets activated by ADP, which indicates that SAA might possess antithrombotic activities [28].…”
Section: Discussionmentioning
confidence: 99%
“…They focused on compounds from three herbs: cimicifugae (Cimicifuga foetida L.), ganoderma (Ganoderma lucidum Karst), and licorice (Glycyrrhiza uralensis Fisch), as some studies have suggested that they demonstrate antithrombosis activity (Yi et al, 2017). Liu et al (2018) performed a similar screening campaign to find novel ligands for P2Y1 and P2Y12 receptors that could be used as antithrombotic drugs. They evaluated 253 compounds from Traditional Chinese Medicines and tested 11 hits through in vitro assays, including salvianolic acids from Salvia militorrhiza (Liu et al, 2018).…”
Section: Molecular Docking and Virtual Screeningmentioning
confidence: 99%
“…Liu et al (2018) performed a similar screening campaign to find novel ligands for P2Y1 and P2Y12 receptors that could be used as antithrombotic drugs. They evaluated 253 compounds from Traditional Chinese Medicines and tested 11 hits through in vitro assays, including salvianolic acids from Salvia militorrhiza (Liu et al, 2018). Table 2 demonstrates some studies that applied virtual screening, using the molecular docking strategy to discover novel ligands for P2 receptors.…”
Section: Molecular Docking and Virtual Screeningmentioning
confidence: 99%
See 1 more Smart Citation